2018
DOI: 10.1002/acm2.12354
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a secondary VOI protocol for lung imaging in a clinical CT scanner

Abstract: We present a solution to meet an unmet clinical need of an in‐situ “close look” at a pulmonary nodule or at the margins of a pulmonary cyst revealed by a primary (screening) chest CT while the patient is still in the scanner. We first evaluated options available on current whole‐body CT scanners for high resolution screening scans, including ROI reconstruction of the primary scan data and HRCT, but found them to have insufficient SNR in lung tissue or discontinuous slice coverage. Within the capabilities of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In this study, we found that the standard high-resolution helical volume chest CT scan with standard reconstruction resolution underestimated the cyst score, due to inability to resolve small cysts, which became visible in high resolution images from a UH re-scan. The UH rescan was optimized in a previous study on a chest phantom that contained lung mimicking and control foams [17]. That study concluded that the UH re-scan maintained the same noise level as the standard HRCT images but at twice the resolution.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we found that the standard high-resolution helical volume chest CT scan with standard reconstruction resolution underestimated the cyst score, due to inability to resolve small cysts, which became visible in high resolution images from a UH re-scan. The UH rescan was optimized in a previous study on a chest phantom that contained lung mimicking and control foams [17]. That study concluded that the UH re-scan maintained the same noise level as the standard HRCT images but at twice the resolution.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the question whether the difference between the standard HRCT scan and the UH re-scan is simply due to the resolution of image reconstruction, this was assessed quantitatively in the previous chest phantom study [17], which found that the HRCT scan reconstructed at the resolution of the UH re-scan had 2.4 times the noise level of the UH re-scan. The increase in noise was consistent with the relative levels of dose concentration between the two scans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations